Cannabinoids for the treatment of refractory neuropathic pruritus in amyotrophic lateral sclerosis: A case report. (January 2022) - Lou, Kelvin; Murphy, Shane; Talbot, Clair
Background: Neuropathic symptoms have a wide variety of manifestations, ranging from pain to pruritus. Neuropathic pruritus is a type of chronic pruritus related to damaged small fibers. Cannabinoids have evidence to manage neuropathic symptoms. We present a case of refractory neuropathic pruritus that was successfully managed with the use of oral cannabinoids. Case presentation: A 60-year-old male with amyotrophic lateral sclerosis with ongoing pruritus despite the use of standard neuropathic therapies. Possible course of action: Sodium channel and N -methyl-D-aspartate receptor antagonists have evidence for neuropathic symptoms but can cause significant gastrointestinal side effects. Prescription cannabinoids such as nabiximol can be cost prohibitive to use in practice. Synthetic tetrahydrocannabinol products are dose limited by psychoactive side effects. Formulation of a plan: A balanced oral cannabinoid from a licensed producer was preferred as it has evidence for neuropathic symptoms and is generally well tolerated. Outcome: The patient showed improvement to his pruritus score from 7/10 to 3/10. There was initial increased sedation but tolerance developed quickly. Lessons learned from case: Cannabinoids are possibly safe and effective in management of neuropathic pruritus. View on research problems: Additional research is needed to establish efficacy and safety.